HUBUNGAN ANTARA SELF-CONTROL DENGAN PERILAKU KONSUMTIF ONLINE SHOPPING PRODUK FASHION PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI ANGKATAN 2011 - Chita, Regina C. M.; David, Lydia; Pali, Cicilia (e-Biomedik, 2015)
Abstract: Self-control on adolescent is the capacity which can be used to control external variables that determine behavior. Conditions of unstable teenage emotions lead them to become consumerists. Teen consumer behavior on fashion products is to support their presentation. Consumer behavior is happening also more facilitated by the existence of Online Shopping. This study aimed to find out whether there was a relationship between self-control with consumer online shopping behavior of fashion products in students faculty of medicine University of Sam Ratulangi force 2011.This study was analytic with cross sectional approach. Sampling techniques are used i.e. consecutive sampling. The respondents were students of Faculty of Medicine University of Sam Ratulangi batch 2011 with a total number of 174 respondents. Data were obtained by using questionnaires self-control and behavior consumer online shopping fashion products. The technique analysis of the test data by using correlation Sperman Rank with error prediction of Î± = 0,05. The results showed that there was a relationship between support self-control by consumer online shopping behavior of fashion products in students faculty of medicine University of Sam Ratulangi force 2011, with test correlation value obtained Sperman Rank p = 0.000 <Î± = 0.05. With the value of the correlation of -0.485 which belong to the category of being. The negative sign indicates the direction of the relationship means the higher self-control then the lower consumer online shopping behavior of fashion products, otherwise the lower self-control then the higher consumer behavior online shopping fashion products. Conclusion: There was a relationship between self-control and consumer online shopping behavior of fashion products among students of Faculty of Medicine University of Sam Ratulangi batch 2011.Keywords: self-control, consumer behavior, online shopping, fashion productsAbstrak: Self-control pada remaja merupakan kapasitas dalam diri yang dapat digunakan untuk mengontrol variabel-variabel luar yang menentukan tingkah laku.Kondisi emosi remaja yang tidak stabil membuat remaja menjadi konsumtif. Perilaku konsumtif remaja pada produk fashion adalah untuk mendukung presentasi mereka. Perilaku konsumtif yang terjadi juga lebih dimudahkan dengan adanya Online Shopping. Penelitian ini bertujuan untuk mencari tahuapakah ada hubungan antara self-control dengan perilaku konsumtif online shopping produk fashion pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi angkatan 2011. Penelitian ini bersifat analitik dengan pendekatan cross sectional. Teknik pengambilan sampel yang digunakan yaitu consecutive sampling. Subyek penelitian adalah mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi angkatan 2011 dengan jumlah 174 responden. Pengambilan data dengan menggunakan kuesioner self-control dan perilaku konsumtif online shopping produk fashion. Teknik analisa data dengan menggunakan uji korelasi Sperman Rank dengan galat pendugaan Î±=0,05. Hasil penelitian didapatkan bahwa terdapat hubungan antara dukungan self-control dengan perilaku konsumtif online shopping produk fashion pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi angkatan 2011, dengan uji korelasi Sperman Rank didapatkan nilai p = 0,000 < Î± = 0,05. Dengan nilai korelasi sebesar -0,485 yang termasuk kedalam kategori sedang. Tanda negatif menunjukan arah hubungan artinya semakin tinggi self-control maka semakin rendah perilaku konsumtif online shopping produk fashion, sebaliknya semakin rendah self-control maka semakin tinggi perilaku konsumtif online shopping produk fashion. Simpulan: Terdapat hubungan antara self-control dengan perilaku konsumtif online shopping produk fashion pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi angkatan 2011Kata kunci: self-control, perilaku konsumtif, online shopping, produk fashion